The impact of modeling on mastering the pictorial composition skills of students of the Department of Art Education (Journal of the College of Basic Education, 2022)
The research aims to reveal the impact of the modeling method on mastering the pictorial composition skills of the students of the Department of Art Education.It was applied to a sample consisting of third-stage students in the College of Basic Education / Al-Mustansiriya University (30) male and female students, with (15) males and (15) females.The tool used to achieve the research objective was the cognitive achievement test and the skill performance evaluation form.The achievement test is characterized by apparent validity and reliability by the Wackeronbach method of (0.89), while the skill performance evaluation form is also characterized by apparent validity and reliability, with an agreement ratio between the arbitrators amounting to (0.86).The most important findings of the research are:The method of learning by modeling contributed to the progress of the performance of technical skills in the subject of pictorial composition through the sequence in presenting information and the gradient in the segmentation of the performance of the skill into sub-skills.